PENGARUH PROFESIONALISME APARATUR TERHADAP KUALITAS PELAYANAN PUBLIK DI KELURAHAN POLOWIJEN - Fitri Puji Rahayu; Lavionita Ezly Kurniawati; Sevilla Deva Aura Aprilia (Juremi: Jurnal Riset Ekonomi, 2024)
Public services are the right of all people without exception. Service quality is a success between the community as service users and the government as service providers. The quality of service is reflected in how public service officers serve the community well and how they continue to strive to provide quality services to the community. The Polowijen Subdistrict Office is one of the areas that still relies on conventional services. Considering that public services are increasing and expanding, every apparatus or bureaucrat must be able to compete and be able to anticipate rapid world developments in various aspects of life so as to improve the quality of service and high performance to realize the professionalism of the apparatus in anticipating the needs of the public service sector